(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2025)
Within the domain of early education, specifically in Tangerang Regency, the deployment of interactive learning mediums presents substantial potential in terms of augmenting pupils’ grasp of intricate topics such as the human reproductive system. The advent of novel technologies, exemplified by the OKY application, signifies a transformative shift towards both engaging and efficacious pedagogical methodologies designed for young students. By integrating interactive components into pedagogical practices, instructors can engender immersive and dynamic educational experiences that accommodate a variety of learning preferences. The origination and execution of the OKY application aspire to overhaul the manner in which elementary students interact with and understand complex scientific notions. Employing a research and development methodology steered by the Dick and Carey framework, the current inquiry endeavours to ascertain the OKY application’s effectiveness in enhancing pupils’ comprehension of the human reproductive system via qualitative evaluations and contrasts of knowledge adaptation pre- and post-application utilization.